Kredit Usaha Rakyat (Kur) Dan Pengaruhnya Terhadap Kinerja Bank (Suatu Studi Kasus) - Ida Bagus Made Agung Dwijatenaya; Bambang Sukma Alam; Fitri Darmawati (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract:This aim of this study was to find out the effect of the effectiveness distribution of Small Businnes Loan Program on the performance in Bank Rakyat Indonesia of Tenggarong Sebarang Branch. The instrument used to assess bank performance is a questionnaire. The sampling technique with the full sampling method. The analytical tool used to test the hypothesis is the Product Statistics Program and Service Solution (SPSS) version 22.0 for Windows. The results of the study showed that the effectiveness of the distribution of Small Businnes Loan Program was the positively response, is that very good. Respondents' responses to the performance of Bank Rakyat Indonesia Tenggarong Sebarang Branch tend to be positive, which is very good. The effectiveness of Small Businnes Loan Program distribution has a positive and significant effect on the Bank's performance. As stated by the government that the Small Businnes Loan Program program is aimed at improving people's welfare. Therefore, it is recommended that the distribution of Small Businnes Loan Program by the Bank always be improved. Keywords : Distribution Effectiveness, Small Businnes Loan Program, Bank Performance